Contribuição do Estudo Aeromagnetométrico e de Imagens Orbitais (TM LANDSAT 5) ao Conhecimento do Arcabouço Geológico do Distrito Fluorítico de Santa Catarina (Brasil) e suas Implicações para a Prospecção de Fluorita - HOFF, ROSEMARY; BASTOS NETO, ARTUR CEZAR; ROLIM, SÍLVIA BEATRIZ ALVES (Pesquisas em Geociências, 2002)
<!-- .p { text-align: justify; } --> Geophysical (aeromagnetometry) and remote sensing (TM LANDSAT) data allowed to recognize different structural patterns at the Santa Catarina fluorite district. These features correspond to N-S and NNE-SSW structural lineaments with potential environments for fluorite prospection. In detail, the used treatment allowed to identificate minor structures associated with these lineaments and showed that two principal structures carring mineralization prolongs themselves for dozens of kilometers in areas where previous existence were not even suspected. So a serie of data were searched about origin, evolution and relative chronology for the structures present in several directions, just like questions about the geological evolution of the district.